Analysis of Illocutionary Acts Performed in to Fluency's Youtube Channel - Isanabiah Isanabiah; Fitrawati Fitrawati (English Language and Literature, 2022)
This study is aimed to find out (1) the types of Illocutionary acts, (2) the most dominant paradigmatic cases and (3) the specific intention of the speakers in Advanced English Conversation video podcasts using the theory proposed by Searle in Huang (2007). This research used the descriptive method. The data of this research were 209 of the selected utterances of Jack and Kate, which potentially performed the types of Illocutionary acts and their paradigmatic cases taken from To Fluency’s YouTube channel as the data source. The first finding showed that all types of Illocutionary acts were performed in the video podcasts. They were representative (98 datum), declarative (8 datum), commissive (8 datum), directive (18 datum), and expressive (77 datum). It can be seen that the most dominant type of Illocutionary acts was representative. Furthermore, the second finding showed that the most dominant paradigmatic case was describing. It was the paradigmatic case of the representative. The frequency of describing in the video podcast about food was 28 times and 19 times in the podcast about jobs. In other words, the speakers specifically intended to describe something they are sure of in the context of food and jobs.